Alas, poor ghost! Traditions of belief in story and discourse - Bennett, Gillian, author; Utah State University Press, publisher (Colorado State University. Libraries, 1999)
In the rational modern world, belief in the supernatural seemingly has been consigned to the worlds of entertainment and fantasy. Yet belief in other worldly phenomena, from poltergeists to telepathy, remains strong, as Gillian Bennett's research shows.
Belief and Disbelief -- Is Belief in the Supernatural Declining? -- Telling It Slant -- Patterns of Belief -- Order in Chaos -- Family Love -- Competing Cultures -- Contact with the Dead -- Life after Death -- Ghosts and Hauntings -- Visitations -- Cause, Consequence, and Lack Liquidated -- Delving -- Witnesses, Bereavement, and the Sense of Presence / Kate Bennett -- Witnesses -- Bereavement -- The Sense of Presence -- From Private Experience to Public Performance Supernatural Experience as Narrative -- Belief and Disbelief: Patterns of Narration -- Story Dialectic: The Imaginary Judge and Jury -- "Alas, Poor Ghost!" Case Studies in the History of Ghosts and Visitations -- The Ghost of Hamlet's Father -- The Cock Lane Poltergeist -- The Clodd/Lang Debate -- The Vanishing Hitchhiker -- A Brief History of "Witnesses" -- Collecting the Data -- The Manchester Study -- The Leicester Study -- Transcribing Spoken Texts -- The Manchester Respondents -- Linguistic Clues to Belief and Disbelief -- Word Lists Showing Story Patterns in Memorates.
New, expanded, and extensively revised edition of Traditions of Belief: Women and the Supernatural.
Keywords: Folklore -- Great Britain; Occultism -- Great Britain; Ghosts -- Great Britain; Women -- Great Britain -- Folklore